Investment Dispersion and the Business Cycle - Bachmann, Rüdiger; Bayer, Christian (American Economic Review, 2014)
The cross-sectional dispersion of firm-level investment rates is procyclical. This makes investment rates different from productivity, output, and employment growth, which have countercyclical dispersions. A calibrated heterogeneous-firm business cycle model with nonconvex capital adjustment costs and countercyclical dispersion of firm-level productivity shocks replicates these facts and produces a correlation between investment dispersion and aggregate output of 0.53, close to 0.45 in the data. We find that small shocks to the dispersion of productivity, which in the model constitutes firm risk, suffice to generate the mildly procyclical investment dispersion in the data but do not produce serious business cycles. (JEL D42, D92, E32, G31, G32)